Effect of Golden Snail-Based Local Microorganisms on the Growth and Yield of Baby Corn - Aida Yanti, Nur; Anwar, Syaifuddin; H, Sudirman; Haswin, Dwi Wahyuni; Nasrul, Muhammad (ITScience (Information Technology and Science), 2025)
The use of local microorganisms (MOL) derived from golden apple snails (Pomacea canaliculata) is a sustainable agricultural innovation that supports plant growth through natural bioactivation. Golden apple snails, often considered pests in rice fields, are rich in protein and minerals, making them suitable substrates for microbial development. Fermenting these snails into MOL provides a natural source of beneficial microbes and nutrients that can improve soil health, enhance nutrient availability, and stimulate plant growth. This study aimed to evaluate the effect of different application doses of golden apple snail-based MOL on the growth and yield of semi-corn (Zea mays L.). The field experiment was conducted at Politeknik Pembangunan Pertanian Gowa using a Randomised Complete Block Design (RCBD) with four treatments and three replications. The treatments consisted of P0 = control (without MOL), P1 = 133 ml MOL/plant, P2 = 160 ml MOL/plant, and P3 = 186 ml MOL/plant. The observed parameters were plant height, number of leaves, ear length, and ear weight. The results showed that MOL application significantly affected plant height, ear length, and ear weight. Among the treatments, P2 produced the highest values for all observed parameters, including plant height (160.67 cm), ear length (13.95 cm), and ear weight (60.63 g). Therefore, a dose of 160 ml/plant of golden apple snail-based MOL is considered optimal for improving semi-corn growth and yield under field conditions.